2014
DOI: 10.11113/jt.v71.3609
|View full text |Cite
|
Sign up to set email alerts
|

Robust Weighted Least Squares Estimation of Regression Parameter in the Presence of Outliers and Heteroscedastic Errors

Abstract: In a linear regression model, the ordinary least squares (OLS) method is considered the best method to estimate the regression parameters if the assumptions are met. However, if the data does not satisfy the underlying assumptions, the results will be misleading. The violation for the assumption of constant variance in the least squares regression is caused by the presence of outliers and heteroscedasticity in the data. This assumption of constant variance (homoscedasticity) is very important in linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…However, MLR has a weakness, namely the problem of classical assumptions. Therefore, robust regression is used to create the best model and avoid the problem of classical assumptions (Pesko and Robarts, 2017;Rasheed et al, 2014) . 4 showed that consumption of one cigarette in rural areas had a positive and significant effect.…”
Section: Methodsmentioning
confidence: 99%
“…However, MLR has a weakness, namely the problem of classical assumptions. Therefore, robust regression is used to create the best model and avoid the problem of classical assumptions (Pesko and Robarts, 2017;Rasheed et al, 2014) . 4 showed that consumption of one cigarette in rural areas had a positive and significant effect.…”
Section: Methodsmentioning
confidence: 99%
“…Penelitian ini telah menggunakan robust pada model regresi linear berganda yang digunakan. Analisis regresi robust menjadi solusi untuk regresi linear agar terhindar dari masalah asumsi klasik (Rasheed et al 2014). Dengan penggunaan regresi robust akan menciptakan model terbaik dan stabil (Thoni et al 1990).…”
Section: Pendahuluanunclassified
“…Penggunaan regresi logistik sangat mirip degan regresi linar berganda dengan pengecualian bahwa variabel terikat pada regresi logistik adalah binomial. Hasil regresi l o g i s t i k a k a n m e n u n j u k k a n r a s i o kemungkinan yang disebabkan dari masingmasing variabel bebas yang diamati (Sperandei, 2014 Penggunaan robust dilakukan pada penelitian ini agar model regresi terhindar dari masalah asumsi klasik (Rasheed, Adnan, Saffari, & Pati, 2014). Hasil yang terbaik akan diperoleh dari penggunaan regresi robust (Thoni, Neter, Wasserman, & Kutner, 1990 Hasil regresi logistik menunjukkan bahwa terdapat 4 variabel yang memperbesar k e m u n g k i n a n s e o r a n g m a h a s i s w a mengkonsumsi rokok elektrik dan rokok konvensional secara bersamaan dan terdapat 2 variabel yang memperkecil kemungkinan seorang mahasiswa mengkonsumsi rokok elektrik dan rokok konvensional secara bersamaan.…”
Section: Metode Penelitianunclassified